Synthesis and Study of Co(II), Ni(II) and Cu(II) Complexes with Schiff Base Ligands Derived from 3-Amino-2-phenyl-4(3H)-quinazoline One - Rai, B.K.; Singh, Vineeta; Vidyarthi, S.N.; Sinha, Puja (Asian Journal of Chemistry, 2011)
In the present work, complexes of hexacoordinated Co(II), Ni(II) and Cu(II) complexes of the type [M(APQH)X2] where M = Co(II), Ni(II) and Cu(II), APQH = 3-amino-2-phenyl-4(3H)- quinazoline hydrazone, X = Cl–, Br–, I– and NO3–. The prepared ligand APQH and its complexes have been characterized by elemental analyses, molar mass, molar conductance, infrared spectra, electronic spectra and magnetic susceptibility measurements. On the basis of above physicochemical observations, the compound APQH acts as a neutral bidentate ligand and coordination proposes through azomethine nitrogen and primary amino group of quinazoline side chain. The remaining position of metal ions are occupied by negative ions such as Cl–, Br–, I– and NO3–. The structure of the complexes are proposed to be octahedral in nature.